Strategi Manajemen Pembentukan Badan Usaha Milik Desa (BUM Desa) - Eka Nuraini (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
Based on preliminary studies in Air Saga Village, the problems faced by villages to form BUM Desa are lack of ability to map village potentials, it is difficulty to find human resources who will manage BUM Desa, lack of understanding to start establishing BUM Desa, and lack of ability to compile BUM Desa administration. These problems must be addressed immediately by conducting research activities aimed at formulating management strategies for the formation of BUM Desa, especially in Air Saga Village. The research method uses qualitative methods with the following steps: (1) conducting observations to obtain information about the potential of the village, (2) conducting interviews with village heads and BPD, (3) conducting FGD. The collected data were analyzed using qualitative descriptive techniques. The results showed that an aggressive strategy is the right strategy to form a BUM Desa in Air Saga Village, Tanjungpandan District, Belitung Regency. The implementation of the strategy for establishing BUM Desa must involve village facilitators and be evaluated in each of its activities